Room temperature thiosulfate ion redox reaction-driven synthesis of a robust porous copper–cobalt–sulfur–oxygen nanowire coating on copper foam for highly-efficient and low-cost oxygen evolution reaction. Issue 59 (5th July 2019) - Wang, Yanqing; Li, Yuemeng; Ding, Liping; Ong, Aaron; Ding, Jun
Abstract : Room temperature thiosulfate ion redox reaction-driven synthesis of robust porous Cu–Co–S–O NWC on copper foam for highly-efficient and low-cost OER. Abstract : A robust porous copper–cobalt–sulfur–oxygen nanowire coating (Cu–Co–S–O NWC) was fabricated for the first time on copper foam using a mild thiosulfate ion redox reaction-driven chemical bath synthesis (CBS) strategy. Cu–Co–S–O NWC has a large ECAS, enriched tunnels for gas and electrolyte diffusion and good electron transfer performance from the highly conductive copper foam substrate, and herein, shows improved overall OER activity, outperforming the precious IrO2 catalyst and almost all the as-reported Cu-based or Co-based catalysts, especially at high current density.